2018
DOI: 10.4067/s0370-41062018000100010
|View full text |Cite
|
Sign up to set email alerts
|

Hipofosfemia en recién nacidos prematuros: un trastorno bimodal

Abstract: New nutritional approaches to treat extreme premature babies have demonstrated relevant eviden ce of metabolic disturbances with early hypophosphatemia, especially in patients with intrauterine growth restriction (IUGR). They have shown late hypophosphatemia, as well, which is characteristic in the metabolic bone disease. A sytematic search of literature describing metabolic disturbances of phosphorus in preterm newborns is presented, related to the use of early parenteral nutrition and also in the context of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Approximately 94% of newborns with birth weight under 1,000 g had hypophosphatemia among them [26]. Tariq et al reported that there was persistent hypercalcemia in very low birth weight newborns, while serum phosphate levels were consistently lower than the normal range (4-8 mg/ dl) [26][27][28][29]. In recent years, early nutritional management of small and premature infants has become increasingly popular due to its beneficial effects on the nervous system [29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Approximately 94% of newborns with birth weight under 1,000 g had hypophosphatemia among them [26]. Tariq et al reported that there was persistent hypercalcemia in very low birth weight newborns, while serum phosphate levels were consistently lower than the normal range (4-8 mg/ dl) [26][27][28][29]. In recent years, early nutritional management of small and premature infants has become increasingly popular due to its beneficial effects on the nervous system [29].…”
Section: Discussionmentioning
confidence: 99%
“…Tariq et al reported that there was persistent hypercalcemia in very low birth weight newborns, while serum phosphate levels were consistently lower than the normal range (4-8 mg/ dl) [26][27][28][29]. In recent years, early nutritional management of small and premature infants has become increasingly popular due to its beneficial effects on the nervous system [29]. However, this nutritional strategy makes them more prone to electrolyte disturbances, including hypophosphatemia.…”
Section: Discussionmentioning
confidence: 99%
“…In turn, uncontrolled chronic hypophosphatemia can cause respiratory and myocardial failure due to ATP depletion of the myocyte, rhabdomyolysis, anemia, hemolysis, seizures, and metabolic acidosis [ 33 ].…”
Section: Discussionmentioning
confidence: 99%